Mitochondrial calcium uniporter complex modulation in cancerogenesis. Issue 10 (19th May 2019) - Marchi, Saverio; Vitto, Veronica Angela Maria; Danese, Alberto; Wieckowski, Mariusz R.; Giorgi, Carlotta; Pinton, Paolo
ABSTRACT: Aberrations in mitochondrial Ca 2+ homeostasis have been associated with different pathological conditions, including neurological defects, cardiovascular diseases, and, in the last years, cancer. With the recent molecular identification of the mitochondrial calcium uniporter (MCU) complex, the channel that allows Ca 2+ accumulation into the mitochondrial matrix, alterations in the expression levels or functioning in one or more MCU complex members have been linked to different cancers and cancer-related phenotypes. In this review, we will analyze the role of the uniporter and mitochondrial Ca 2+ derangements in modulating cancer cell sensitivity to death, invasiveness, and migratory capacity, as well as cancer progression in vivo. We will also discuss some critical points and contradictory results to highlight the consequence of MCU complex modulation in tumor development.